Method for electrochemically synthesizing ammonia and used polymer solid electrolyte

By introducing nanotitanium dioxide filler into polymer solid electrolytes for electrochemical synthesis of ammonia, the problems of high energy consumption and low selectivity in the prior art are solved, and the effect of efficient electrochemical synthesis of ammonia under low temperature conditions is achieved.

CN119640328AActive Publication Date: 2025-03-18ZHEJIANG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411745266.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-18
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing electrochemical ammonia synthesis method requires high temperature conditions, high energy consumption and is not conducive to the collection of ammonia gas, and there is a competitive reaction to hydrogen evolution reaction using aqueous electrolytes, resulting in a decrease in selectivity.

Method used

The sulfonated polyether etherketone (SPEEK) polymer solid electrolyte containing nanotitanium dioxide (TiO2) filler is used to improve proton conductivity by introducing nanotitanium dioxide into the polymer electrolyte, and a high-performance solid electrolyte film is formed through an improved preparation method.

Benefits of technology

Under low temperature conditions, the ammonia gas generation rate is significantly improved, energy consumption is reduced, the mechanical strength and chemical stability of the electrolyte are enhanced, and the selectivity of the reaction is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of materials, in particular to a polymer solid electrolyte which is a sulfonated polyether ether ketone (SPEEK) polymer solid electrolyte containing a nano titanium dioxide (TiO2) filler. The invention also provides a preparation method of the polymer solid electrolyte. The invention also provides a method for electrochemically synthesizing ammonia by using the polymer solid electrolyte. According to the invention, nitrogen and water are taken as raw materials, the polymer solid electrolyte which can be applied to electrochemical synthesis of ammonia under normal pressure is developed, and the ammonia yield can be improved under the reaction condition of low temperature (80-120 DEG C).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a method for electrochemically synthesizing ammonia and a method for preparing a SPEEK polymer solid electrolyte containing nano-TiO2 filler used therein. Background Art

[0002] Solid electrolyte refers to a solid conductive material that conducts electricity through ion displacement. Due to the defects in the crystal lattice of the material, this type of material has good conductivity under high temperature conditions, which can promote reaction kinetics, improve the current efficiency and stability of the catalyst, and obtain a higher ammonia production rate. It is attempted to be applied to the electrocatalytic ammonia synthesis reaction.

[0003] Solid electrolytes used in electrochemical synthesis of ammonia include proton conductors and oxygen ion conductors. In recent years, people have conducted extensive research on proton conductors as electrolytes for electrochemical synthesis of ammonia. Chen et al. (Journal of Alloys and Compounds, 2009, 485(1): 69-72) synthesized Gd-doped BaCeO3 (BaCe 0.85 G 0.15 O 3-δ , BCGO), with BCGO as electrolyte, Ni-BCGO and Ag-Pd alloy as anode and cathode respectively, N2 and H2 as reaction raw materials, the ammonia generation rate at 480℃ is 4.63×10 -9 mol cm -2 s -1 Similarly, Liu et al. (SolidState Ionics, 2006, 177(1-2):73-76) used Ce 0.8 Sm 0.2 O 2-δ (SDC) as electrolyte and Ag-Pd alloy as electrode, the ammonia generation rate at 650℃ is 8.2×10 -9 mol·cm- 2 ·s -1 However, common proton conductors such as perovskite, pyrochlore and fluorite need to work at higher temperatures to show higher proton conductivity. In order to reduce the operating temperature of electrochemical ammonia synthesis, composite proton conductors and polymer materials are used as electrolytes. Lan et al. (Science Reports, 2013, 3: 1-7) used H + / NH4 + The electrochemical synthesis of ammonia with different reaction materials at room temperature was studied using Nafion 211 membrane as electrolyte and Pt / C as catalyst for cathode and anode. When N2 and H2 were used as reactants, the ammonia generation rate could reach 3.1×10 -9mol cm -2 ·s -1 ; When air and H2O are reactants, the rate of ammonia generation is 1.14×10 - 9 mol cm -2 ·s -1 , realizing the electrochemical synthesis of ammonia directly from air and H2O at room temperature and pressure. However, due to the limitation of low temperature, its ammonia production rate is low.

[0004] According to existing literature and technology, the use of solid electrolytes for electrochemical synthesis of ammonia mostly uses high-temperature proton conductors and is carried out under high temperature conditions (i.e.), which consumes a lot of energy and is not conducive to the collection of product ammonia.

[0005] At present, the electrochemical synthesis of ammonia using nitrogen and water as raw materials uses an aqueous electrolyte, which has a serious competing reaction, the hydrogen evolution reaction, resulting in a decrease in the selectivity of the reaction. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a green and mild method for electrochemically synthesizing ammonia using nitrogen and water and a polymer solid electrolyte used therein.

[0007] In order to solve the above technical problems, the present invention provides a polymer solid electrolyte, which is a sulfonated polyetheretherketone (SPEEK) polymer solid electrolyte containing nano titanium dioxide (TiO2) filler.

[0008] The present invention also provides a method for preparing the above polymer solid electrolyte, comprising the following steps:

[0009] 1) Under the protection of an inert gas (such as nitrogen), polyetheretherketone (PEEK) is subjected to a sulfonation reaction using sulfuric acid (concentrated sulfuric acid) to obtain sulfonated polyetheretherketone (SPEEK);

[0010] 2) Dissolve 10 g of sulfonated polyetheretherketone (SPEEK) in an ethanol / water solution at 60-80° C. to obtain a polymer solution;

[0011] 3) Disperse 0.5-5 g (preferably 0.8-2 g) of nano titanium dioxide (TiO2) filler in 50±10 mL of ethanol to obtain a TiO2 dispersion;

[0012] 4) Under stirring conditions, add the TiO2 dispersion obtained in step 3) to the polymer solution obtained in step 2) (slowly, and the slow addition time is controlled within 30 to 60 seconds). After the addition is completed, continue stirring for 12±2 hours to ensure sufficient mixing;

[0013] 5) Add 0.8-1.2 g of ammonium hydrogen nitrate (NH4NO3) to the mixed solution obtained in step 4) and stir evenly (so that the ammonium ions are evenly distributed in the polymer); then pour into a flat-bottomed container (maintaining the liquid depth of about 2-4 mm), and then let it stand (standing time is about 24-48 hours) to evaporate the solvent (ethanol and water) to form a uniform polymer film;

[0014] 6) Drying the polymer film obtained in step 5) at 70-90° C. to constant weight;

[0015] The dried film is then treated in boiling water for 1±0.1 h (to activate its proton conductivity) to obtain a SPEEK / TiO2 solid electrolyte film as a polymer solid electrolyte.

[0016] As an improvement to the method for preparing the polymer solid electrolyte of the present invention: in the ethanol / water solution of step 2), the volume ratio of ethanol to water is 1:0.9 to 1.1 (preferably 1:1).

[0017] As a further improvement of the preparation method of the polymer solid electrolyte of the present invention, the step 1) is:

[0018] Dissolve 100 g of polyetheretherketone (PEEK) in 280-320 mL (preferably 300 mL) of concentrated sulfuric acid and stir at room temperature for 24±2 h to achieve sulfonation reaction;

[0019] After the reaction is completed, the reaction mixture is poured into ice water (excess ice water) to terminate the reaction, and the resulting precipitate is washed with water (repeatedly washed with distilled water until the washing liquid is neutral), and then vacuum dried (vacuum dried at 50-70°C to constant weight) to obtain sulfonated polyetheretherketone (SPEEK).

[0020] As a further improvement of the preparation method of the polymer solid electrolyte of the present invention, step 2) is:

[0021] At 60-80° C., add 10 g of sulfonated polyetheretherketone (SPEEK) to 900-1100 mL of ethanol / water solution, and stir to dissolve for 24±2 h to obtain a polymer solution.

[0022] As a further improvement of the method for preparing the polymer solid electrolyte of the present invention, in the step 3):

[0023] According to the material-liquid ratio of 0.8-2 g nano titanium dioxide (TiO2) / 50 mL ethanol, nano titanium dioxide (TiO2) is added into ethanol and dispersed (ultrasound can be used for dispersion) to obtain a TiO2 dispersion (evenly dispersed TiO2 dispersion).

[0024] The present invention also provides a method for electrochemically synthesizing ammonia using the polymer solid electrolyte prepared by the above method, comprising the following steps:

[0025] 1. Establish an electrolytic cell between the anode and the cathode, place the SPEEK / TiO2 solid electrolyte film in the electrolytic cell as an electrolyte, and the SPEEK / TiO2 solid electrolyte film separates the electrolytic cell into a cathode side and an anode side;

[0026] 2. A gas mixture containing nitrogen and water vapor is introduced into the cathode side of the electrolytic cell, and electrolysis is performed at a set potential and temperature to promote an electrochemical reaction between nitrogen and water to generate ammonia; at the same time, proton (hydrogen ion) transfer is performed in the electrolyte to maintain the reaction; and ammonia generated during the electrochemical synthesis process is collected.

[0027] Description: In the present invention, the SPEEK / TiO2 solid electrolyte film plays an isolating role in the electrolytic cell, so that the nitrogen and water vapor mixture on the cathode side is separated from the gas (generated oxygen) on the anode side. Nitrogen is used as a reactant, and water is used as a proton source and water molecules in the electrolyte. Ammonia is generated on the cathode side of the electrolytic cell by the electrochemical reaction of nitrogen and water, and is discharged from the cathode side along with the gas flow; after gas-liquid separation, the ammonia is collected by a conventional condensation device, and the yield is calculated by detection (gas chromatography-mass spectrometry).

[0028] As an improvement of the method for electrochemical synthesis of ammonia of the present invention:

[0029] The volume ratio of nitrogen to water is 1:3;

[0030] The potential range is set to -5.0 to 0 V (preferably -1.0 to -2.0 V), and the reaction temperature is set to 80 to 120° C. (preferably 80 to 100° C.).

[0031] The reaction time (electrolysis time) can be set to, for example, 10 to 20 hours.

[0032] In order to develop a milder process, the present invention uses nitrogen and water as raw materials and develops a polymer solid electrolyte that can be used for electrochemical synthesis of ammonia under normal pressure, which can increase its ammonia production under low temperature (80-120°C) reaction conditions.

[0033] Compared with the prior art, the present invention has the following advantages:

[0034] 1) By introducing nano-titanium dioxide (TiO2) into the polymer electrolyte, the proton conductivity is significantly improved, thereby improving the efficiency of the electrochemical reaction.

[0035] 2) Nano-TiO2 fillers enhance the mechanical strength of the polymer film, increasing the tensile strength of the polymer film from 20 MPa without fillers to 45 MPa, while also improving the chemical stability of the polymer film, with the performance still maintaining more than 95% of the original after 500 hours of use.

[0036] 3) SPEEK electrolyte allows the reaction system to operate at a lower temperature (80-120°C), reducing energy consumption and material costs.

[0037] 4) The use of solid electrolytes in the present invention can avoid side reactions caused by the presence of water and can effectively improve selectivity. DETAILED DESCRIPTION

[0038] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process.

[0039] In the present invention, the particle size of nano titanium dioxide (TiO2) is 10 to 50 nanometers; the concentration of concentrated sulfuric acid is 98%.

[0040] Example 1: A method for preparing a SPEEK / TiO2 solid electrolyte film:

[0041] 1) Under nitrogen protection, 100 g of polyetheretherketone (PEEK) was dissolved in 300 mL of concentrated sulfuric acid and stirred at room temperature for 24 hours to achieve sulfonation reaction.

[0042] After the reaction is completed, the reaction mixture is poured into an excess (1000 mL) of ice water to terminate the reaction and obtain a precipitate. The precipitate is repeatedly washed with distilled water until the washing liquid is neutral. The washed precipitate is dried in a vacuum drying oven (60°C vacuum drying to constant weight) and sulfonated polyetheretherketone (SPEEK) is set aside.

[0043] 2) Dissolve 10 g of SPEEK in a mixed solution of 500 mL of distilled water and 500 mL of ethanol, and stir and dissolve at 60° C. for 24 hours to form a uniform polymer solution.

[0044] 3) Disperse 1 g of nano titanium dioxide (TiO2) filler in 50 mL of ethanol and use ultrasonic treatment for 30 minutes to ensure that TiO2 is evenly dispersed in the ethanol; obtain a TiO2 dispersion.

[0045] 4) Under stirring conditions, slowly add the TiO2 dispersion obtained in step 3) to the polymer solution obtained in step 2), and the slow addition time is controlled within 30 to 60 seconds to ensure that the nano-TiO2 is evenly distributed in the polymer solution; after the addition is completed, continue stirring for 12 hours to ensure sufficient mixing.

[0046] 5) Add 1 g of ammonium hydrogen nitrate (NH4NO3) to the mixed solution obtained in step 4) and stir evenly to make the ammonium ions evenly distributed in the polymer; then pour it into a flat-bottomed glass container (keep the depth of the solution at about 2 mm), and let it stand for about 24 hours to evaporate the solvent (ethanol and water) to form a uniform polymer film.

[0047] 6) Drying the polymer film obtained in step 5) at 80° C. to a constant weight, thereby removing moisture;

[0048] The dried film was treated in boiling water for 1 h to activate its proton conductivity to obtain a SPEEK / TiO2 solid electrolyte film.

[0049] Note: Drying to constant weight at 80°C can not only remove most of the water and solvent residues, but also uniform drying can avoid stress concentration or microcracks in the membrane due to uneven distribution of water or solvent, ensuring that the membrane is not prone to defects such as rupture in subsequent processing steps. In other words, pre-drying can keep the membrane in a more stable structure when entering the boiling water treatment, avoid sudden volume changes, and ensure the controllability of the treatment process and the final performance of the membrane.

[0050] Experiment 1: Electrochemical synthesis of ammonia

[0051] Referring to the battery test system used in Example 1 of CN202111139571.X "A solid electrolyte for electrocatalytic oxygen reduction synthesis of hydrogen peroxide and its preparation method", an electrolytic cell is established between the anode and the cathode, oxidized carbon black is sprayed on the anion exchange membrane on the cathode, and 60% Pt / C is sprayed on the proton exchange membrane on the anode; the prepared SPEEK / TiO2 solid electrolyte film is placed in the electrolytic cell as an electrolyte; the SPEEK / TiO2 solid electrolyte film separates the electrolytic cell into the cathode side and the anode side.

[0052] A gas mixture containing nitrogen and water vapor (the volume ratio of nitrogen and water is 1:3) is introduced to the cathode side of the electrolytic cell at a flow rate of 50 mL / min. The SPEEK / TiO2 solid electrolyte film acts as an isolation in the electrolytic cell, separating the nitrogen and water vapor mixture on the cathode side from the gas (generated oxygen) on the anode side. Nitrogen is used as a reactant, and water is used as a proton source and water molecules in the electrolyte. Electrolysis is performed at a set potential of -1.0 V for 10 hours, and the reaction temperature is set to 100°C, prompting an electrochemical reaction between nitrogen and water to generate ammonia.

[0053] Ammonia is generated on the cathode side of the electrolytic cell through the electrochemical reaction of nitrogen and water, and is discharged from the cathode side along with the airflow. After gas-liquid separation, ammonia is collected through a conventional condensation device, and the yield is calculated through detection. The ammonia generation rate is 9.5×10 -8 mol cm -2 ·s -1 .

[0054] The detection can be carried out by gas chromatography-mass spectrometry technology, in which a gas mixture (including nitrogen and ammonia) is passed into a gas chromatograph, and then the mass spectrum characteristic peak of ammonia is detected by a mass spectrometer, and the amount of ammonia generated is calculated based on its peak area.

[0055] The calculation formula of ammonia generation rate is NH3 =n NH3 / (A×t).

[0056] n NH3 is the number of moles of ammonia generated (mol), A is the effective area of ​​the electrode (i.e., the battery cathode area, cm 2 ), t is the reaction time s.

[0057] Example 2: A method for preparing a SPEEK / TiO2 solid electrolyte film, with the following changes compared to Example 1:

[0058] Change the stirring temperature in step 2) from "60°C" to "70°C";

[0059] The rest is the same as Example 1.

[0060] The SPEEK / TiO2 solid electrolyte film obtained in Example 2 was used to electrochemically synthesize ammonia according to Experiment 1, and the ammonia generation rate was 9.2×10 -8 mol cm -2 ·s -1 .

[0061] Example 3: A method for preparing a SPEEK / TiO2 solid electrolyte film, with the following changes compared to Example 1:

[0062] The amount of nano titanium dioxide (TiO2) filler in step 3) is changed from "1g" to "0.8g", and the rest is the same as Example 1.

[0063] The SPEEK / TiO2 solid electrolyte film obtained in Example 3 was subjected to electrochemical synthesis of ammonia according to Experiment 1, and the ammonia generation rate was 8.5×10 -8 mol cm -2 ·s -1 .

[0064] Example 4: Preparation method of SPEEK / TiO2 solid electrolyte film, with the following changes compared to Example 1:

[0065] The amount of nano titanium dioxide (TiO2) filler in step 3) is changed from "1g" to "2g", and the rest is the same as Example 1.

[0066] The SPEEK / TiO2 solid electrolyte film obtained in Example 3 was used to electrochemically synthesize ammonia according to Experiment 1, and the ammonia generation rate was 6.7×10 -8 mol cm -2 ·s -1 .

[0067] Experiment 2: Change the reaction temperature in Experiment 1 from "100°C" to "90°C", and the rest is the same as Experiment 1.

[0068] The SPEEK / TiO2 solid electrolyte films obtained in Examples 1 and 2 were subjected to electrochemical synthesis of ammonia according to Experiment 2. The results are shown in Table 1 below.

[0069] Experiment 3: Change the set potential in Experiment 1 from "-1.0 V" to "-2.0 V", and change the reaction temperature from "100°C" to "80°C"; the rest is the same as Experiment 1.

[0070] The SPEEK / TiO2 solid electrolyte films obtained in Examples 1 and 2 were subjected to electrochemical synthesis of ammonia according to Experiment 3. The results are shown in Table 1 below.

[0071] Comparative Experiment 1: Change the reaction temperature in Experiment 1 from "100°C" to "20°C"; the rest is the same as Experiment 1.

[0072] The SPEEK / TiO2 solid electrolyte film obtained in Example 1 was used to electrochemically synthesize ammonia according to Comparative Experiment 1, and the ammonia generation rate was 1.2×10 -10 mol cm -2 ·s -1 。

[0073] Table 1. Ammonia generation rates (mol·cm) of different solid electrolyte films under different experimental conditions -2 ·s -1 )

[0074] Example 1 Example 2 Example 3 Example 4 Experiment 1 <![CDATA[9.5×10 -8 ]]> <![CDATA[9.2×10 -8 ]]> <![CDATA[8.5×10 -8 ]]> <![CDATA[6.7×10 -8 ]]> Experiment 2 <![CDATA[8.5×10 -8 ]]> <![CDATA[8.7×10 -8 ]]> / / Experiment 3 <![CDATA[8.2×10 -8 ]]> <![CDATA[8.3×10 -8 ]]> / / Comparative experiment 1 <![CDATA[1.2×10 -10 ]]> / / /

[0075] Note: “ / ” means the experiment was not conducted.

[0076] Comparative Example 1: Preparation of SPEEK solid electrolyte film:

[0077] The following changes are made relative to Example 1:

[0078] Cancel steps 3) and 4);

[0079] That is, 1 g of ammonium hydrogen nitrate (NH4NO3) is directly added to the polymer solution obtained in step 2);

[0080] The rest is the same as in Example 1; a SPEEK solid electrolyte membrane is obtained.

[0081] The SPEEK solid electrolyte film obtained in Comparative Example 1 was subjected to electrochemical synthesis of ammonia according to Experiment 1, and the ammonia generation rate obtained was 1.8×10 -9 mol cm -2 ·s -1 .

[0082] Comparative Example 2: The filler in Example 1 is changed from nano titanium dioxide (TiO2) to nano CeO2, and the amount used remains unchanged, still 1 g, and the rest is the same as Example 1.

[0083] The SPEEK / CeO2 solid electrolyte film obtained in Comparative Example 2 was subjected to electrochemical synthesis of ammonia according to Experiment 1, and the ammonia generation rate obtained was 1.5×10 -9 mol cm -2 ·s -1 .

[0084] Comparative Example 3-1: Change the amount of "ammonium hydrogen nitrate (NH4NO3)" in step 5) of Example 1 from "1 g" to "1.5 g", and the rest is the same as Example 1.

[0085] The SPEEK / TiO2 solid electrolyte film obtained in Comparative Example 3-1 was subjected to electrochemical synthesis of ammonia according to Experiment 1, and the ammonia generation rate obtained was 2.8×10 -9 mol cm -2 ·s -1 .

[0086] Comparative Example 3-2: The amount of "ammonium hydrogen nitrate (NH4NO3)" in step 5) of Example 1 was changed from "1 g" to "0.5 g", and the rest was the same as Example 1.

[0087] The SPEEK / TiO2 solid electrolyte film obtained in 3-2 was used to electrochemically synthesize ammonia according to Experiment 1, and the ammonia generation rate was 2.9×10 -9 mol cm -2 ·s -1 .

[0088] Comparative Example 4: The step of "drying at 80°C to constant weight" in step 6) of Example 1 was eliminated, that is, the product obtained in step 5) was directly subjected to boiling water treatment, and the rest was the same as Example 1.

[0089] The SPEEK / TiO2 solid electrolyte film obtained in Comparative Example 4 was subjected to electrochemical synthesis of ammonia according to Experiment 1, and the ammonia generation rate obtained was 5.8×10 -9 mol cm -2 ·s -1 .

[0090] Comparative Example 5: Change the amount of "nano titanium dioxide (TiO2) filler" in step 3) of Example 1 from "1g" to "0.2g", and the rest is the same as Example 1.

[0091] The SPEEK / TiO2 solid electrolyte film obtained in Comparative Example 5 was subjected to electrochemical synthesis of ammonia according to Experiment 1, and the ammonia generation rate obtained was 1.6×10 -10 mol cm -2 ·s -1 .

[0092] Comparative Example 6: Change "500 mL of distilled water and 500 mL of ethanol" in Example 1 to "300 mL of distilled water and 700 mL of ethanol", and the rest is the same as Example 1.

[0093] The SPEEK / TiO2 solid electrolyte film obtained in Comparative Example 6 was subjected to electrochemical synthesis of ammonia according to Experiment 1, and the ammonia generation rate obtained was 3.6×10 -10 mol cm -2 ·s -1

[0094] Experiment 4, stability comparison:

[0095] The SPEEK / TiO2 solid electrolyte film obtained in Example 1 was used to electrochemically synthesize ammonia according to Experiment 1. After continuous use for 500 hours, the ammonia generation rate still remained above 95% of the original rate.

[0096] However, when the SPEEK solid electrolyte film obtained in Comparative Example 1 was used to electrochemically synthesize ammonia according to Experiment 1, after continuous use for 500 hours, the ammonia generation rate could only maintain 56% of the original rate.

[0097] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A polymer solid electrolyte, characterized in that: It is a sulfonated polyetheretherketone polymer solid electrolyte containing nano-titanium dioxide filler.

2. The method for preparing a polymer solid electrolyte according to claim 1, characterized in that The following steps are involved: 1) Under the protection of inert gas, polyetheretherketone is subjected to sulfonation reaction using sulfuric acid to obtain sulfonated polyetheretherketone; 2) Dissolve 10 g of sulfonated polyetheretherketone in an ethanol / water solution at 60-80° C. to obtain a polymer solution; 3) Disperse 0.5-5 g of nano titanium dioxide filler in 50±10 mL of ethanol to obtain a TiO2 dispersion; 4) Add the TiO2 dispersion obtained in step 3) to the polymer solution obtained in step 2) under stirring conditions. After the addition is completed, continue stirring for 12±2h to ensure sufficient mixing; 5) Add 0.8-1.2 g of ammonium hydrogen nitrate to the mixed solution obtained in step 4) and stir evenly; then pour into a flat-bottomed container and let stand to evaporate the solvent to form a polymer film; 6) Drying the polymer film obtained in step 5) at 70-90° C. to constant weight; The dried film is then treated in boiling water for 1±0.1 h to obtain a SPEEK / TiO2 solid electrolyte film as a polymer solid electrolyte.

3. The method for preparing a polymer solid electrolyte according to claim 2, characterized in that: In the ethanol / water solution of step 2), the volume ratio of ethanol to water is 1:0.9-1.

1.

4. The method for preparing a polymer solid electrolyte according to claim 3, characterized in that The step 1) is: Dissolve 100 g of polyetheretherketone in 280-320 mL of concentrated sulfuric acid and stir at room temperature for 24 ± 2 h to achieve sulfonation reaction; After the reaction is completed, the reaction mixture is poured into ice water to terminate the reaction, and the obtained precipitate is washed with water and then dried in vacuum to obtain sulfonated polyetheretherketone.

5. The method for preparing a polymer solid electrolyte according to claim 4, characterized in that The step 2) is: At 60-80° C., add 10 g of sulfonated polyetheretherketone to 900-1100 mL of ethanol / water solution, and stir to dissolve for 24±2 h to obtain a polymer solution.

6. The method for preparing a polymer solid electrolyte according to claim 5, characterized in that In the step 3): Nano-titanium dioxide is added into ethanol and dispersed according to a material-liquid ratio of 0.8-2 g nano-titanium dioxide / 50 mL ethanol to obtain a TiO2 dispersion.

7. A method for electrochemically synthesizing ammonia using a polymer solid electrolyte prepared by any one of claims 2 to 6, characterized in that The following steps are involved:

1. Establish an electrolytic cell between the anode and the cathode, place the SPEEK / TiO2 solid electrolyte film in the electrolytic cell as an electrolyte, and the SPEEK / TiO2 solid electrolyte film separates the electrolytic cell into a cathode side and an anode side; 2. A gas mixture containing nitrogen and water vapor is introduced into the cathode side of the electrolytic cell, and electrolysis is performed at a set potential and temperature to promote an electrochemical reaction between nitrogen and water to generate ammonia; at the same time, proton transfer is performed in the electrolyte to maintain the reaction; and ammonia generated during the electrochemical synthesis process is collected.

8. The method for electrochemically synthesizing ammonia according to claim 7, characterized in that: The volume ratio of nitrogen to water is 1:3; The potential range is set to -5.0 to 0 V, and the reaction temperature is set to 80 to 120°C.

9. The method for electrochemically synthesizing ammonia according to claim 8, characterized in that: Potential -1.0~-2.0V, reaction temperature 80~100℃.

Citation Information

Patent Citations

  • Solid electrolyte applied for synthesizing hydrogen peroxide through electrocatalytic oxygen reduction, and preparation method thereof

    CN113809375A

  • Preparation method of composite proton exchange membrane for all vanadium redox flow battery

    CN102945972A

  • Phosphorylation titanium dioxide hollow sphere-filled sulfonated polyether ether ketone film as well as preparation and application

    CN103304979A

  • Sulfonated polyetheretherketone / amino-functionalized TiO2 hybrid membrane, as well as preparation and applications of hybrid membrane

    CN103554831A

  • Highly-sulfonated polyether-ether-ketone and graphene oxide copolymer material and proton exchange membrane preparation method thereof

    CN107946619A